Relationship between creativity and academic achievement: a study of gender differences - Naderi, Habibollah; Abdullah, Rohani; Tengku Abdul Hamid, Tengku Aizan; Sharir, Jamaluddin; Vijay, Kumar Mallan (Marsland Press, 2010)
The objective of this research is to examine if a relationship exists between creativity and academic achievement and if the relationship differs between males and females. Two research questions are examined in this paper: (1) what is the relationship between different aspects of creativity and academic achievement? (2) Is there any significant gender differences regarding the relationship between different aspects of creativity and academic achievement? Participants (N= 153; male = 105 and female = 48) completed creativity test. Cumulative grade point average (CGPA) was used to select the participants. Creativity was measured using the Khatena-Torrance Creative Perception Inventory (KTCPI). Pearson Correlation analysis indicated that aspects of creativity are related to academic achievement for both males and females. However, implications of the findings for this study in creativity and academic achievement are discussed.